Trophic position determines functional and phylogenetic recovery after disturbance within a community. (29th March 2017) - Fountain‐Jones, Nicholas M.; Jordan, Gregory J.; Burridge, Christopher P.; Wardlaw, Timothy J.; Baker, Thomas P.; Forster, Lynette; Petersfield, Morgana; Baker, Susan C.
Summary: The roles that functional traits and/or evolutionary history of species from co‐occurring trophic groups have in determining community recovery following disturbance are poorly understood. Functional traits help determine how species interact with their environment, thus functional traits are likely to change with time since logging. However, traits of species may also be phylogenetically constrained depending on their evolutionary history. Because beetles are trophically diverse, the effects of phylogenetic and functional aspects of community recovery can be compared between co‐occurring trophic groups. Using a chronosequence of forest ages following logging, we applied a novel combination of functional trait and phylogenetic approaches to assess the extent to which taxonomic, functional and phylogenetic composition recovered after logging, and if these dimensions of composition approached those characteristic of mature forests, for both predators and decomposers/primary consumers. We also examined to what extent functional traits of both trophic groups were phylogenetically conserved. Predator functional composition had recovered ∼45 years after logging, and this recovery preceded taxonomic recovery. Neither taxonomic nor functional composition had recovered for the decomposer/primary consumer communities by this time. In contrast to decomposers/primary consumers, predator community recovery had no distinct phylogenetic signature, yet predator functional traits were more phylogenetically conserved than decomposers/primary consumer functional traits. Trait syndromes that characterise forest recovery stages are identified and provide a basis for future work on community re‐assembly following disturbance. We demonstrate differential recovery of co‐occurring beetle trophic groups following disturbance. We show that functional and phylogenetic composition may be disconnected from taxonomic composition; highlighting the advantages of integrating understanding of these three potentially independent components of ecological diversity to enable deeper understanding of animal community composition. Abstract : Lay Summary